Lluvia raincoat backpack / Akmal Fahmi Mohammad Zamri … [et al.] - Mohammad Zamri, Akmal Fahmi; Abd Jalil, Aiedeel; Rahmat, Athirah Ayuni; Mohd Puzi, Nur Hidayah; Asmadi, Nurul Nurina; Jamil, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
LLUVIA is delighted to be a pioneer in the development of a new and distinctive product that will surely influence the bag and raincoat industry's trends. This product is named after the company’s name, which translates to "rain" in Spanish. Our product combines two products into one, namely a bag and a raincoat. It's been created to work together, with the bag acting as a tool for carrying our possessions and the raincoat acting as a lifesaver when it's raining. The company illustrates how combining two products into a single item might save money over buying two items individually. Malaysia's weather may be fickle. Malaysia is, without a doubt, a hot nation due to its location on the equator (Garisan Khatulistiwa). Because of our high humidity, big rains arrive at the most inconvenient times. In the morning, a dazzling sky can be seen. However, as time passes, the sky gradually darkens. People do not bother bringing their umbrellas in the morning since the sky appears to be so brilliant. Raincoat backpack is another alternative for people to avoid bad weather. Our raincoat is made from polyester microfiber material, a special waterproof coating which makes it perfect to protect us from rain. Raincoat backpack not only protects ourselves but also our belongings such as laptops, tabs and smartphones. Imagine the chaotic hustle when you are rushing to go to class or office and both of your hands are already full with carrying items that may not be suitable to be kept in the bag. People frequently forget to bring their umbrellas, or they may believe that taking an umbrella adds to the load of whatever they are carrying at the time. Problems may be solved in the blink of an eye now that Lluvia Raincoat Backpack has hit the market.